Perovskite microcells fabricated using swelling-induced crack propagation for colored solar windows - Lee, Woongchan; Yoo, Young Jin; Park, Jinhong; Ko, Joo Hwan; Kim, Yeong Jae; Yun, Huiwon; Kim, Dong Hoe; Song, Young Min; Kim, Dae-Hyeong (Nature Communications, 2022)
Perovskite microcells have a great potential to be applied to diverse types of optoelectronic devices including light-emitting diodes, photodetectors, and solar cells. Although several perovskite fabrication methods have been researched, perovskite microcells without a significant efficiency drop during the patterning and fabrication process could not be developed yet. We herein report the fabrication of high-efficiency perovskite microcells using swelling-induced crack propagation and the application of the microcells to colored solar windows. The key procedure is a swelling-induced lift-off process that leads to patterned perovskite films with high-quality interfaces. Thus, a power conversion efficiency (PCE) of 20.1 % could be achieved with the perovskite microcell, which is nearly same as the PCE of our unpatterned perovskite photovoltaic device (PV). The semi-transparent PV based on microcells exhibited a light utilization efficiency of 4.67 and a color rendering index of 97.5 %. The metal–insulator–metal structure deposited on the semi-transparent PV enabled to fabricate solar windows with vivid colors and high color purity. Perovskite microcells can be applied to various types of optoelectronic devices. Here, authors report high efficiency perovskite microcells fabricated using swelling-induced crack propagation and demonstrate solar windows using the microcells.